1998
DOI: 10.1111/j.1540-8191.1998.tb01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Left Ventriculectomy in Patients with Dilated Failing Ventricle

Abstract: Lateral PLV improved hemodynamics and functional capacity as much as aneurysmectomy by reducing ventricular volume and mitral regurgitation. Inclusion and exclusion criteria have to be sought to make PLV safer and more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 10 publications
1
27
0
3
Order By: Relevance
“…Other indicators for a worse outcome included fractional shortening <5% and duration of preoperative symptoms >9 years. Individual centers have also implicated degree of postoperative mitral regurgitation [56]and extent of interstitial fibrosis [57]as adverse factors affecting outcome. However, it still remains difficult to predict which candidates are virtually guaranteed a successful outcome.…”
Section: Reconstruction For Dilated Cardiomyopathymentioning
confidence: 99%
“…Other indicators for a worse outcome included fractional shortening <5% and duration of preoperative symptoms >9 years. Individual centers have also implicated degree of postoperative mitral regurgitation [56]and extent of interstitial fibrosis [57]as adverse factors affecting outcome. However, it still remains difficult to predict which candidates are virtually guaranteed a successful outcome.…”
Section: Reconstruction For Dilated Cardiomyopathymentioning
confidence: 99%
“…5 They also compared NYHA class I patients with those of NYHA class II, III or IV and found no difference between the groups with respect to preoperative LVDd, postoperative LVDd or absolute reduction of LV end-diastolic diameter. Kawaguchi et al described poor results of extended partial left ventriculectomy concomitant with excision of the papillary muscle and mitral valve followed by implantation of a bioprosthesis, 6 suggesting that greater volume reduction and less mitral regurgitation does not necessarily improve function. They also reported that patients having less severe interstitial fibrosis of the excised myocardium showed a better prognosis than patients with more severe fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…O emprego da ventriculectomia parcial esquerda, como uma alternativa ao transplante cardíaco, no tratamento de pacientes portadores de cardiomiopatia dilatada tem sido investigado com grande interesse em centros nacionais e internacionais, cuja experiência inclui, atualmente, mais de mil casos operados em todo o mundo (2,4,(6)(7)(8)(9)(10)(11)13,15) . A interpretação dos resultados obtidos em vários estudos, no entanto, é limitada pela existência de ventricular em 5 anos de seguimento da ventriculectomia parcial esquerda no tratamento da cardiomiopatia dilatada.…”
Section: Comentáriosunclassified
“…Rev Bras Cir Cardiovasc 2001; 16(4): 275-88. Meses de Seguimento % afecções de diversas etiologias nas séries relatadas (2,(7)(8)(9)(10)(11)15) e pela associação da redução cirúrgica do volume do VE a outros procedimentos, além da correção da insuficiência valvar mitral (2,(7)(8)(9)(10)15) .…”
Section: Comentáriosunclassified
See 1 more Smart Citation